HUBUNGAN PENGETAHUAN LINGKUNGAN HIDUP DENGAN KEMAMPUAN PEMECAHAN MASALAH PENCEMARAN LINGKUNGAN PADA SISWA SMAN 6 TANGERANG - Diana Vivanti Sigit; Ernawati Ernawati; Mariatul Qibtiah (Biosfer: Jurnal Pendidikan Biologi, 2017)
Environment knowledge is collection of facts, information and the principles of concerning something that there are around living things. Environment knowledge related to problem solving skills that is the process of applying of knowledge which has previously obtained into a new situation unknown. The purpose of this study is to find correlation environment knowledge with the problem solving skills about environmental pollution. The study was conducted in April-May 2016 at SMAN 6 Tangerang. The research methodology was survey with the study correlation. Samples were taken at random with Simple Random Sampling technique, as many as 127 students of science tenth grade. Prerequisite test showed data normal and homogeny. Regression model Å¶ = 24,24 + 1,10X that significance and had a linier correlation. Correlation values obtained 0,42 which was sufficient criteria. Coefficient of determination test showed that 17,62% of environmental knowledge contribute to the problem solving about environmental pollution. The conclution of this study there was positive correlation between environmental knowledge and problem solving environmental pollution.